(untitled) (Ameghiniana, 2014)
Jurassic fishes are described from southern South America, from Argentina and Chile only. Six species and several undescribed fish group& are known from these localities. Each species is restricted to one specific locality. The holosteans Lepidotes and Pachycormus, and the pholidophorid Pholidophorus occur in the Northern Hemisphere, too, while the teleosts genera and families are found in South America only